Efficacy of interventions to reduce coercive treatment in mental health services: umbrella review of randomised evidence. (April 2021) - Barbui, Corrado; Purgato, Marianna; Abdulmalik, Jibril; Caldas-de-Almeida, José Miguel; Eaton, Julian; Gureje, Oye; Hanlon, Charlotte; Nosè, Michela; Ostuzzi, Giovanni; Saraceno, Benedetto; Saxena, Shekhar; Tedeschi, Federico; et al.
Abstract : Background: Coercive treatment comprises a broad range of practices, ranging from implicit or explicit pressure to accept certain treatment to the use of forced practices such as involuntary admission, seclusion and restraint. Coercion is common in mental health services. Aims: To evaluate the strength and credibility of evidence on the efficacy of interventions to reduce coercive treatment in mental health services. Protocol registration: https://doi.org/10.17605/OSF.IO/S76T3 . Method: Systematic literature searches were conducted in MEDLINE, Cochrane Central, PsycINFO, CINAHL, Campbell Collaboration, and Epistemonikos from January 2010 to January 2020 for meta-analyses of randomised studies. Summary effects were recalculated using a common metric and random-effects models. We assessed between-study heterogeneity, predictive intervals, publication bias, small-study effects and whether the results of the observed positive studies were more than expected by chance. On the basis of these calculations, strength of associations was classified using quantitative umbrella review criteria, and credibility of evidence was assessed using the GRADE approach. Results: A total of 23 primary studies (19 conducted in European countries and 4 in the USA) enrolling 8554 participants were included. The evidence on the efficacy of staff training to reduce use of restraint was supported by the most robust evidence (relative risk RR = 0.74, 95% CI 0.62–0.87; suggestive association, GRADE: moderate), followed by evidence on the efficacy of shared decision-making interventions to reduce involuntary admissions of adults with severe mental illness (RR = 0.75, 95% CI 0.60–0.92; weak association, GRADE: moderate) and by the evidence on integrated care interventions (RR = 0.66, 95% CI 0.46–0.95; weak association, GRADE: low). By contrast, community treatment orders and adherence therapy had no effect on involuntary admission rates. Conclusions: Different levels of evidence indicate the benefit of staff training, shared decision-making interventions and integrated care interventions to reduce coercive treatment in mental health services. These different levels of evidence should be considered in the development of policy, clinical and implementation initiatives to reduce coercive practices in mental healthcare, and should lead to further studies in both high- and low-income countries to improve the strength and credibility of the evidence base.